Serous borderline ovarian tumors (clinical features, morphology, treatment) - I. Yu. Davydova; V. V. Kuznetsov; A. I. Karseladze (ABV-press, 2014)
This article considers the clinical features, morphology and general conteporary principles of treatment of ovarian serous borderline tumors. Despite to presence of several malignant signs in borderline ovarian tumors, disease rather has favorable outcome. It allows to perform the conservative surgery for patient in reproductive age, preserve ovarian tissue and save fertility.